A drift on liposomes to proliposomes: recent advances and promising approaches. (2nd October 2022) - Dhiman, Neha; Sarvaiya, Jayrajsinh; Mohindroo, Poorti
Abstract: Liposomes are nano-structured vesicles, made up of phospholipids that provide active ingredients at the site of action at a predetermined rate and add the advantage of the sustained-release formulation. Liposomes have stability issues that tend to agglomerate and fuse upon storage, which reflects their drawback. Hence to overcome the aggregation, fusion, hydrolysis, and/or oxidation problems associated with liposomes a new technology named Proliposomes has been introduced. Proliposomes are defined as carbohydrate carriers coated with phospholipids, which upon addition of water generate liposomes. The objective of the review is to cover the concept of proliposomes for pulmonary or alveolar delivery of drugs and compare it with that of liposomes; highlight the methods used for preparations along with the characterization parameters. This is the first systematic review that covers the categorization of liposomes, characteristic methods, and recent examples of drugs from 2015 to 2021, supplied in form of proliposomes to the macrophages as well as others and offers an advantage over the free drug by offering a prolonged drug release and sufficient bioavailability in addition to overcome the stability issues related to liposomes. Since this is a very new technology and many scientists are continuously working in this field to make the drug available for clinical trials and ultimately in the market for the targeted delivery of drugs with better storage life. HIGHLIGHTS: Proliposomes as an alternative to overwhelm the stability and storage-related issues of liposomes. Anhydrous carbohydrate carriers are utilized for proliposomal preparation. Inhaled delivery of drugs as solid lipid nanoparticles offers a significant impact on pulmonary tract infections, particularly in cystic fibrosis. Size of liposomes attained after proliposome hydrolysis is critical for drug delivery via respiration.